Twitch - Morris, Tee 1968- (John Wiley & Sons, Inc., 2022)
Twitch For Dummies will get you up to date with Twitch, the breakthrough streaming platform where you can set up a channel, increase your viewership, and find your people. Step-by-step guides and helpful, real-life examples get you ready to go live and, who knows, maybe even earn a little money while having fun online. Check out this new edition for all the details on the new Creator Dashboard interface, streaming in the metaverse, and details you need to know to get the world watching. This handy reference even covers the latest Twitch integrations for streaming from your mobile devices. Community-based entertainment has never been hotter, and Dummies shows you how to get on board. This is the perfect Dummies guide for new and established Twitch streamers who want to improve their audience and skills.
Includes index
Keywords: Twitch (Electronic resource); Webcasting; Streaming video; Webdiffusion; Vidéo en continu; streaming video